Applicability and cross-cultural adaptation of the self-administered Child–OIDP in a rural Nigeria community (2017)
The utilization of the Child Oral Impact on Daily Performances (Child–OIDP), one of the most widely used quality of life measures for children, in rural communities will require cross adaptation of the measure since rural communities in Africa are in no small way influenced by the prevailing cultural norms and values. The aim of this study was to assess the applicability of self administered Child–OIDP measure in a rural Community in Nigeria. A cross sectional study was conducted among 403 secondary school students in Igboora, Nigeria using self-administered Child–OIDP questionnaire translated into the local language. The mean age of the study participants was 12.4 (±0.7) years. The impact of oral health on their daily performances scores ranged from 0 to 66. Higher OIDP scores were significantly associated with perceived need for dental treatment (p < 0.001), satisfaction ratings of oral health condition (p = 0.001), satisfaction ratings of tooth appearance (p = 0.030) and pain (p < 0.001). The use of frequency or severity scales separately or combined exhibited similar and acceptable validity and reliability; however, the frequency scale alone had the highest Cronbach’s alpha value (0.876), while use of both frequency and severity scales was best for inter–item correlations (0.552-0.714). The translated version of the Child–OIDP measure is a valid and applicable tool in a rural community. Use of either the frequency or severity scale of this version of Child–OIDP is valid, cross-culturally adaptable and recommended